High-field EPR detection of a disulfide radical anion in the reduction of cytidine 5′-diphosphate by the E441Q R1 mutant of Escherichia coli ribonucleotide reductase - Lawrence, Christopher C. (The National Academy of Sciences, 1999)
Class I ribonucleotide reductases (RNRs) are composed of two subunits, R1 and R2. The R2 subunit contains the essential diferric cluster–tyrosyl radical (Y⋅) cofactor and R1 is the site of the conversion of nucleoside diphosphates to 2′-deoxynucleoside diphosphates. A mutant in the R1 subunit of Escherichia coli RNR, E441Q, was generated in an effort to define the function of E441 in the nucleotide-reduction process. Cytidine 5′-diphosphate was incubated with E441Q RNR, and the reaction was monitored by using stopped-flow UV-vis spectroscopy and high-frequency (140 GHz) time-domain EPR spectroscopy. These studies revealed loss of the Y⋅ and formation of a disulfide radical anion and present experimental mechanistic insight into the reductive half-reaction catalyzed by RNR. These results support the proposal that the protonated E441 is required for reduction of a 3′-ketodeoxynucleotide by a disulfide radical anion. On the minute time scale, a second radical species was also detected by high-frequency EPR. Its g values suggest that this species may be a 4′-ketyl radical and is not on the normal reduction pathway. These experiments demonstrate that high-field time-domain EPR spectroscopy is a powerful new tool for deconvolution of a mixture of radical species.